AN EVALUATION OF CLIMATE CHANGE FROM A LEGAL PERSPECTIVE OF TURKEY IN THE SCOPE OF INTERNATIONAL LAW (The Proceedings of The International Conference on Climate Change, 2021)
Climate change is a global emergency. Each country's efforts and responses to climate change are of significance individually. The dynamics behind their attitudes are needed to be understood to harmonize global response. Turkey is of a different legal approach than the international community generally. For instance, it is the only G20 country that is not a party to the Paris Agreement. Also, the legal perspective of Turkey is of particular significance for the European Union to achieve its targets. Thus, the question of international legal steps taken and the next steps by Turkey arises. To evaluate this situation, the legal frameworks are analyzed with specific reference to Turkey. It was found that Turkey has been demanding to be recognized as a developing country in the international climate instruments. Although Turkey put some afford to act against climate change, it was not seen as adequate by scientific reports. Also, international and regional human rights instruments have been invoked by individuals for the current policies of Turkey and legal proceedings were started. For an efficient response to climate change, key points regarding common but differentiated responsibilities, the relationships between international and national laws, and the importance of laws with comparing regulations and political instruments are addressed to see how these points can inform recommendations. It is concluded that the ratification of the Paris Agreement is required in the first place. Then, enriched legal perspective in international law, and new specific climate laws in national laws are a necessity to provide a meaningful legal response to this global threat. It is hoped that other legal systems may benefit from analyzing its legal perspective. Every country needs to contribute to the shared enterprise of combatting climate change if the future of humanity and the natural world is to be assured.
Keywords: Climate Change; Turkey; International Law; the Paris Agreement